Processing quality of potato tubers produced during autumn and spring and stored at different temperatures - Freitas,Sergio T de (2012)
The objective of this work was to access processing quality of potato clones (Solanum tuberosum) Asterix, SMINIA793101-3, and Missaukee cultivated during spring and autumn growing seasons and stored at 4, 8, 12, or 25ºC. Clones grown in spring had shorter dormancy than clones grown in autumn. Potato tubers grown in spring and autumn and stored at 4ºC, as well as tubers grown in autumn and stored at 8ºC had no sprouting for six months. Among clones grown in autumn, the longest dormancy period during storage at 12ºC was observed in the clone SMINIA793101-3, and at 25ºC was in the clone Asterix. In potato tubers grown in spring, the longest dormancy period during storage at 8ºC was observed in the clones SMINIA793101-3 and Missaukee, at 12ºC was in the clone SMINIA793101-3, and at 25ºC was in the clones Asterix and Missaukee. Potato tubers grown in spring had higher dry matter, starch content, and respiration rates, and lower reducing sugar, and total polyphenol content. The only exception was the Missaukee that had similar dry matter content in both growing seasons. In general, storage at 4ºC and 8ºC were more effective in reducing respiration rates and maintaining higher dry mater content of potato tubers. Chip darkening, reducing sugars, and total polyphenol content increased during storage of potato tubers. Darker chip color, higher reducing sugars and polyphenol content were obtained during storage at temperatures of 4ºC and 8ºC. These results suggest that the best storage temperature depends on genotype, tuber physiological age, and growing conditions.